Perioperative Intravenous Patient-Controlled Analgesic Efficacy of Morphine with Combined Nefopam and Parecoxib versus Parecoxib in Gynecologic Surgery: A Randomized, Double-Blind Study - Varinee Lekprasert; Lapuskorn Yapanan; Wichai Ittichaikulthol; Rungrawan Buachai; Phimol Soisod; Areepan Sophonsritsuk (Anesthesiology Research and Practice)
Background. Nefopam is a non-NSAIDs and opioid sparing centrally acting drug which is effective for a multimodal postoperative analgesia. The present study aimed to evaluate the analgesic efficacy of nefopam combined with parecoxib for gynecologic surgery. Methods. This randomized double-blinded control trial recruited participants (n = 72) who underwent gynecologic surgeries and divided them into either a nefopam or control group. The study group received parecoxib 40 mg plus nefopam 20 mg, while the control group received parecoxib 40 mg plus normal saline solution intravenously during open abdominal gynecological surgery. Both groups then received either nefopam or normal saline every 6 hours postoperatively for 24 hours. Intravenous patient-controlled analgesia with morphine was given for breakthrough pain within 24 h. The participants were evaluated for morphine consumption within 24 hours and postoperative pain using a verbal numerical rating scale (VNRS) at a postanesthetic care unit, at 6-, 12-, and 24-hour postoperative periods. Adverse effects were recorded. Results. Morphine consumption within 24 hours and adverse effects were not significantly different between both groups. Mean difference and 95% confident interval of morphine consumption between both groups was 1.00 (−4.56, 4.76), P=0.97. The VNRS on movement at 6 hours after surgery of the nefopam group was significantly different from that of the control group [mean (SD), 4.14 (2.11) vs. 5.14 (1.80), P=0.04]. The VNRS of the nefopam group at 12 hours after operation during resting and on movement was significantly different from that of the control group ([mean (SD), 1.47 (1.80) vs. 2.54 (2.15), P=0.03], [mean (SD), 3.22 (1.84) vs 4.17 (1.74), P=0.03]), respectively. Conclusions. The combined administration of nefopam and parecoxib during gynecologic surgery slightly reduced the VNRS at 6 and 12 hours postoperatively more than treatment with parecoxib.